TEKNIK SKIPPING SEBAGAI UPAYA MENINGKATKAN PEMAHAMAN ISI BACAAN MELALUI PERPUSTAKAAN ONLINE SISWA KELAS VII MTS DAARUS SALAM - Melina Cristanti Putri; Kholik (Lembaga Penerbitan dan Publikasi Ilmiah (LP2I), 2025)
This study aims to describe how the implementation of using the skipping technique is an effort to improve reading content comprehension through online libraries (class VII students of MTs Daarus Salam Bantur). This research is a descriptive qualitative research. This study aims to increase students' reading speed and students' reading comprehension. With the skipping technique as an effort to increase understanding of reading content, it is hoped that it will be able to increase students' reading interest, reading speed and reading comprehension. Applying speed reading skills is very important for the development of science and technology today. The ability to read fast is a type of reading that prioritizes speed, without leaving an understanding of aspects of reading. The results of this study are expected to be useful for students and future researchers to conduct similar research related to speed reading techniques in learning Indonesian and reading literacy activities.